The Effectiveness of Project-Based Learning in Improving Collaborative Skills of Elementary School Students - Widiharto Purnomo; Xie Guilin; Lusiana Rahmadani Putri (Yayasan Adra Karima Hubbi, 2024)
The development of collaborative skills is a crucial component in preparing elementary school students for future challenges in the 21st century. However, traditional instructional methods often fail to provide sufficient opportunities for students to practice and enhance these skills. To address this issue, Project-Based Learning (PBL) has emerged as an innovative teaching approach that fosters student collaboration through real-world tasks. This study aims to examine the effectiveness of PBL in improving the collaborative skills of elementary school students. The research employed a quasi-experimental design with two groups of students: one group engaged in PBL activities and the other in traditional learning methods. Data were collected through observation, collaboration rubrics, and student feedback over the course of six weeks. The sample consisted of 60 students from grade 5 in an elementary school in Jakarta. Statistical analysis revealed a significant improvement in the collaborative skills of students who participated in PBL activities compared to those in the control group. Students demonstrated better communication, problem-solving, and teamwork abilities. The findings suggest that PBL effectively enhances students' collaborative skills and can be integrated into the elementary school curriculum to promote these essential abilities. Further research is recommended to explore the long-term impact of PBL on other skills, such as critical thinking and creativity.